Optimization of the Preparation Conditions of Aluminum-Impregnated Food Waste Biochar Using RSM with an MLP and Its Application in Phosphate Removal - Kang, Jin Kyu; Kingkhambang, Khonekeo; Lee, Chang Gu; Park, Seong Jik (Water (Switzerland), 2023)
Phosphorus is an essential macroelement in plant growth and the human body, but excessive water enrichment with phosphorus is a global threat to water quality. To address this problem, the development of an efficient, affordable adsorbent for use in removing large amounts of phosphorus from eutrophic water is necessary. Food-waste-based adsorbents offer a sustainable solution because they utilize waste as a valuable resource. This study explored the use of food waste biochar as a novel adsorbent with additional aluminum impregnation (Al–FWB) to enhance its phosphate adsorption capacity. This study employed response surface methodology (RSM) to optimize the synthetic conditions of the Al–FWB with the highest phosphate adsorption capacity. To enhance the identification of the optimal conditions using RSM, this study employed quadratic equations and a multi-layer perceptron (MLP). The pyrolysis temperature and Al concentration significantly (p < 0.05) affected the adsorption capacity of the AL–FWB. The optimal conditions for the preparation of the AL–FWB were a pyrolysis temperature, duration, and Al concentration of 300 °C, 0.5 h, and 6%, respectively, based on the quadratic equation and MLP models. X-ray photoelectron spectroscopy revealed that phosphate was adsorbed on the surface of the AL–FWB via the formation of AlPO4. The optimized AL–FWB (Opt-AL–FWB) removed 99.6% of the phosphate and displayed a maximum phosphate adsorption capacity of 197.8 mg/g, which is comparable to those reported in previous studies. Additionally, the phosphate adsorption capacity of the Opt-AL–FWB was independent of the pH of the solution, and the presence of 10 mM SO42– decreased its adsorption capacity by 15.5%. The use of the Opt-AL–FWB as an adsorbent provides not only efficient phosphate removal but also green, economical food waste reusability. In summary, this study demonstrates the potential of AL–FWB as an effective, sustainable, and affordable adsorbent for use in phosphate removal from contaminated water.
Keywords: Aluminum impregnation; Biochar; Food waste; Multilayers perceptrons; Optimal conditions; Optimisations; Phosphate adsorption capacity; Phosphate removal; Quadratic equations; Response-surface methodology; aluminum impregnation; biochar; food waste; multi-layer perceptron; optimization; phosphate removal; response surface methodology